2017
DOI: 10.1007/s00484-017-1371-8
|View full text |Cite
|
Sign up to set email alerts
|

The rise of phenology with climate change: an evaluation of IJB publications

Abstract: In recent decades, phenology has become an important tool by which to measure both the impact of climate change on ecosystems and the feedback of ecosystems to the climate system. However, there has been little attempt to date to systematically quantify the increase in the number of scientific publications with a focus on phenology and climate change. In order to partially address this issue, we examined the number of articles (original papers, reviews and short communications) containing the terms 'phenology'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 287 publications
0
20
0
Order By: Relevance
“…Previous studies have shown that temporal changes in plant phenology are among the most sensitive indicators of ecological response to climate change. [1216;21;41] Here we show that such alteration in plant phenology is associated with increased prevalence of hay fever among U.S. adults. This is, to our knowledge, the first national scale assessment linking climate driven alteration in plant phenology with prevalence of hay fever in the contiguous United States.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have shown that temporal changes in plant phenology are among the most sensitive indicators of ecological response to climate change. [1216;21;41] Here we show that such alteration in plant phenology is associated with increased prevalence of hay fever among U.S. adults. This is, to our knowledge, the first national scale assessment linking climate driven alteration in plant phenology with prevalence of hay fever in the contiguous United States.…”
Section: Discussionmentioning
confidence: 69%
“…Seasonal changes affect plants and animals, resulting in phenological shifts that can be reconstructed to study climate change and determine seasonality (Donnelly & Yu, ). However, the number of records and methods that are suitable to reliably disentangle past seasonal climate components is limited.…”
Section: Introductionmentioning
confidence: 99%
“…There is a need to study variation in weather characteristics before and during the breeding period in birds in order to understand the ecological implications of climate change and more frequent extreme weather events (Charmantier et al 2008; Goodenough et al 2011; Pipoly et al 2013; Donnelly and Yu 2017; Marrot et al 2017). Extreme weather events are seen as weather conditions that cause the biological response to be in the 5% of most extreme values of the response variable (Altwegg et al 2017; van de Pol et al 2017).…”
Section: Introductionmentioning
confidence: 99%